Power storage device and exterior material for power storage device

The exterior material for all-solid batteries with a gas barrier and sealant layer, featuring precise opening formation, addresses gas leakage and cooling issues by ensuring high accuracy in opening creation and heat dissipation.

JP2025014400APending Publication Date: 2025-01-30LISSENOK PACKAGING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023116920
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Existing all-solid batteries face challenges in forming openings in the sealant layer with high dimensional accuracy due to the difficulty in accurately grasping the border between the sealant layer and the remaining part, leading to issues with gas leakage and insufficient cooling properties.

Method used

The exterior material for power storage devices is designed with a gas barrier layer, a sealant layer, and an adhesive layer, where the sealant layer has planned openings formed with precise removal using an adhesive coating unit and an unpainted unit, ensuring high accuracy in forming openings.

Benefits of technology

This design allows for accurate formation of openings in the sealant layer, preventing gas leakage and enhancing cooling properties by ensuring efficient heat dissipation, while maintaining the structural integrity and insulation of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014400000001_ABST
    Figure 2025014400000001_ABST
Patent Text Reader

Abstract

To provide an exterior material for a power storage device which can accurately form an opening in a sealant layer.SOLUTION: There is provided an exterior material for a power storage device in which a base material layer 11, a metal foil layer 12, a gas barrier layer 13, an adhesive layer 14, and a sealant layer 15 are laminated. The sealant layer 15 is provided with an opening scheduled part 2a where an opening 2 is scheduled to be formed by removing a resin for a sealant layer, and the adhesive layer 14 is provided with an adhesive non-coated part 14b provided corresponding to the opening scheduled part 2a, and an adhesive coating part 14a provided corresponding to a part other than the opening scheduled part. A gloss value of the gas barrier layer 13 is 100 or less.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electricity storage device such as an all-solid-state battery used as a high-power battery such as an in-vehicle battery, a battery for portable devices such as a mobile electronic device, or a battery for storing regenerative energy, and an exterior material for the electricity storage device. [Background technology]

[0002] All-solid-state batteries use solid electrolytes, so there is no risk of electrolyte leakage or dendrites, and the separator is not damaged. Therefore, there is no risk of fire caused by separator damage, and so they are attracting a lot of attention from the perspective of safety.

[0003] A typical all-solid-state battery is configured by sealing an all-solid-state battery body, such as an electrode active material and a solid electrolyte, inside an exterior material serving as a casing. As research into solid electrolytes in this all-solid-state battery progresses, it has gradually become apparent that the performance required of the exterior material differs from that of exterior materials for batteries using conventional liquid electrolytes, and various exterior materials have been proposed to satisfy the performance requirements for all-solid-state batteries.

[0004] The exterior material for an all-solid-state battery has a basic structure including a metal foil layer and a heat-sealing layer (sealant layer) laminated on the inside of the metal foil layer, and the all-solid-state battery body is encapsulated by heat-sealing the sealant layer.

[0005] For example, the all-solid-state battery packaging material shown in Patent Document 1 below has a protective film interposed between a metal foil layer and a sealant layer, and uses a sealant layer with high hydrogen sulfide gas permeability. Furthermore, the all-solid-state battery packaging material shown in Patent Document 2 uses a sealant layer with low hydrogen sulfide gas permeability. Furthermore, the all-solid-state battery packaging material shown in Patent Document 3 uses a sealant layer that absorbs gas. Furthermore, the all-solid-state battery packaging material shown in Patent Document 4 is configured by laminating a vapor deposition film layer on the inner surface of the sealant layer.

[0006] However, the sulfide-based all-solid-state battery that is expected to have the above-mentioned high capacity has a problem in that gas such as hydrogen sulfide gas generated by the reaction between the solid electrolyte and moisture may leak.

[0007] On the other hand, in all-solid-state batteries, the exchange of electrons (ions) occurs through the solid electrolyte during charging and discharging, so the resistance value is higher and the amount of heat generated is greater than that of liquid electrolytes. However, it is believed that the performance of all-solid-state batteries is not affected even in high-temperature environments, and the current situation is that no consideration has been given to high-temperature countermeasures (cooling properties) including those in the above Patent Documents 1 to 4. However, as battery technology advances toward higher output and higher capacity, it is fully predicted that in the future, improved cooling properties will also be required for all-solid-state batteries.

[0008] Therefore, the applicant of the present application has proposed an all-solid-state battery capable of preventing leakage of hydrogen sulfide gas and the like while ensuring sufficient cooling performance, as disclosed in Patent Document 5 below.

[0009] In this all-solid-state battery, the exterior material is configured by sequentially laminating a metal foil layer, a gas barrier layer, and a sealant layer on the inner surface side of a base layer, and an opening is formed in the sealant layer to expose the gas barrier layer to the inside. In this all-solid-state battery, the gas barrier layer prevents leakage of hydrogen sulfide gas and the like, while the opening is formed to improve cooling performance.

[0010] In this all-solid-state battery, an opening is formed by removing a part (a portion to be opened) of the sealant layer in the packaging material sheet in which the sealant layer is laminated over the entire inner surface of the gas barrier layer. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Patent No. 6777276 [Patent Document 2] Patent No. 6747636 [Patent Document 3] Patent Publication No. 2020-187855 [Patent Document 4] Patent Publication No. 2020-187835 [Patent Document 5] International Publication No. 2023 / 022087 Summary of the Invention [Problem to be solved by the invention]

[0012] However, because the exterior material of an all-solid-state battery is composed of a film-like laminate (laminate sheet), it is difficult to accurately grasp the boundary between the part of the sealant layer to be removed (the part to be opened) and the part to be left, and this makes it difficult to properly remove the sealant layer corresponding to the opening, resulting in the problem that it is difficult to form an opening with excellent dimensional accuracy.

[0013] Although the issues in all-solid-state batteries have been described above, similar issues may arise in other power storage devices.

[0014] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide an electricity storage device and an exterior material for an electricity storage device that can reliably form an opening with excellent dimensional accuracy in a sealant layer. [Means for solving the problem]

[0015] In order to solve the above problems, the present invention comprises the following means.

[0016] [1] An exterior material for an electricity storage device, comprising: a resin base layer; a metal foil layer laminated on an inner surface side of the base layer; a gas barrier layer laminated on the inner surface side of the metal foil layer; and a resin sealant layer laminated on the inner surface side of the gas barrier layer via an adhesive layer, the sealant layer is provided with a planned opening portion into which an opening is to be formed by removing a sealant layer resin; the adhesive layer is provided with an adhesive-uncoated portion that is provided in correspondence with the intended opening portion and in which no adhesive is present, and an adhesive-coated portion that is provided in correspondence with a portion other than the intended opening portion and in which adhesive is present; An exterior material for an electricity storage device, wherein the gas barrier layer has a gloss value of 100 or less when measured at an incidence angle of 60° in accordance with JIS Z 8741:1997.

[0017] [2] An exterior material for an electrical storage device with an opening, characterized in that the sealant layer in the exterior material for an electrical storage device described in the preceding paragraph 1 has an opening formed in which the resin for the sealant layer in the intended opening portion has been removed.

[0018] [3] An electricity storage device comprising the exterior material for an electricity storage device according to the preceding paragraph 1 and an electricity storage device main body exteriorly covered with the exterior material for an electricity storage device, An opening is formed in the sealant layer of the electrical storage device exterior material by removing the sealant layer resin from the intended opening portion, and The power storage device, wherein the opening is disposed opposite to the power storage device body.

[0019] [4] A case body having a recessed storage portion in which the power storage device body is stored, and a closing member attached to the case body in a state in which the closing member closes an open portion of the storage portion, 4. The electricity storage device according to item 3, wherein at least one of the case body and the closing member is made of the exterior material for an electricity storage device. Effect of the Invention

[0020] According to the exterior material for an electricity storage device of invention [1], light incident on the adhesive-coated portion is less likely to be diffused by the surface of the gas barrier layer, while light incident on the adhesive-uncoated portion is more likely to be scattered by the surface of the gas barrier layer. Therefore, by setting the gloss value of the gas barrier layer low, the difference in the amount of light between the light reflected from the adhesive-coated portion and the light reflected from the adhesive-uncoated portion becomes larger. When part of the sealant layer is removed to form an opening, the boundary position between the adhesive-coated portion and the adhesive-uncoated portion can be more accurately grasped by a photoelectric sensor or the like, and the sealant layer can be more accurately cut along that boundary position.

[0021] According to the exterior material for an electricity storage device with an opening of the invention [2], it is possible to form an opening with high precision in the sealant layer, similar to the above invention [1].

[0022] According to the electricity storage devices of the inventions [3] and [4], it is possible to form openings with high precision in the sealant layer, similar to the invention [1] above. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an all-solid-state battery as an electricity storage device according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged schematic cross-sectional view showing a main part of FIG. [Diagram 3] FIG. 3 is an exploded perspective view illustrating a schematic diagram of the all-solid-state battery according to the embodiment. [Figure 4] FIG. 4 is a schematic cross-sectional view showing an exterior material for a case body in the all-solid-state battery according to the embodiment. [Figure 5A] FIG. 5A is a schematic inner surface view for explaining a method for detecting an opening in an exterior material according to an embodiment. [Figure 5B] FIG. 5B is a schematic cross-sectional view for explaining a method for detecting an opening in the exterior material of the embodiment. [Figure 6] FIG. 6 is a schematic cross-sectional view illustrating a method for forming an opening in the exterior material of the embodiment. [Figure 7]FIG. 7 is a schematic cross-sectional view showing a mold device for molding a case body using an exterior material with an opening according to an embodiment. [Figure 8] FIG. 8 is a schematic cross-sectional view showing an all-solid-state battery according to a first modified example of the present invention. [Figure 9] FIG. 9 is a schematic cross-sectional view showing an all-solid-state battery according to a second modified example of the present invention. [Figure 10] FIG. 10 is a schematic cross-sectional view showing an all-solid-state battery according to a third modified example of the present invention. [Figure 11] FIG. 11 is a schematic cross-sectional view showing an all-solid-state battery according to a fourth modified example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Fig. 1 is a schematic cross-sectional view showing an all-solid-state battery as an electricity storage device according to an embodiment of the present invention, Fig. 2 is a schematic cross-sectional view showing an enlarged view of a main part of Fig. 1, and Fig. 3 is an exploded perspective view showing a schematic view of the all-solid-state battery according to the embodiment. As shown in these figures, the all-solid-state battery according to this embodiment includes a case body 3 and a blocking member 4 as a casing, and an all-solid-state battery body 5 housed and sealed in the casing.

[0025] 4 is a schematic cross-sectional view showing an exterior material 1 constituting a case body 3 in an all-solid-state battery according to an embodiment. As shown in the figure, the exterior material 1 includes a base layer 11 disposed on the outermost side, a metal foil layer 12 laminated and bonded to the inner surface side of the base layer 11 via a first adhesive layer (not shown), a heat-resistant gas barrier layer 13 laminated and bonded to the inner surface side of the metal foil layer 12 via a second adhesive layer (not shown), and a sealant layer 15 laminated and bonded to the inner surface side of the gas barrier layer 13 via a third adhesive layer 14. In the present invention, when describing the positions of the layers constituting the exterior material 1 in terms of directions, the direction of the base layer 11 (upper side in FIG. 4) is referred to as the outer side, and the direction of the sealant layer (thermal fusion resin layer) 15 (lower side in FIG. 4) is referred to as the inner side.

[0026] The exterior material 1 constituting the blocking member 4 also has a similar structure to the exterior material 1 constituting the case body 3 described above.

[0027] The case body 3 is formed of a molded body of the exterior material 1, and integrally includes a top wall 31, a side wall (circumferential side wall) 32 extending downward from the outer periphery of the top wall 31, and a flange 33 provided on the outer periphery of the lower end of the side wall 32. A storage section 35 is formed inside the top wall 31 and the side wall 32. The blocking member 4 is formed of a sheet-like exterior material 1. The all-solid-state battery body 5 is accommodated in the accommodation section 35 of the case body 3, and the blocking member 4 is arranged so as to close the lower end open part of the accommodation section 35. The blocking member 4 is arranged so that its sealant layer 15 faces inward (upper side), and the sealant layer 15 of the flange 33 of the case body 3 and the sealant layer 15 of the outer periphery of the blocking member 4 are overlapped opposite each other. The overlapped sealant layers 15 are joined and integrated by thermal adhesion (heat sealing), thereby producing an all-solid-state battery in which the all-solid-state battery body 5 is accommodated in a sealed state in the casing (case body 3 and blocking member 4).

[0028] In addition, the case body 3 of the all-solid-state battery has an opening 2 in which the resin constituting the sealant layer 15 and the adhesive constituting the adhesive layer 14 are not present in a portion corresponding to the storage portion 35. Furthermore, the closing member 4 also has an opening 2 in which the resin for the sealant layer and the adhesive for the adhesive layer are not present in a portion corresponding to the storage portion 35. Then, through the opening 2 of the case body 3 and the closing member 4, the gas barrier layer 13 of the exterior material 1 is exposed inside the storage portion 35 and is disposed so as to face the all-solid-state battery body 5.

[0029] In addition, in the all-solid-state battery of this embodiment, a tab lead is provided for taking out electricity, although not shown in the drawings. One end (inner end) of this tab lead is adhesively fixed to the all-solid-state battery body 5, and the middle part is arranged so that it passes through the heat-sealed part between the flange 33 of the case body 3 and the outer circumferential edge part of the blocking member 4, and the other end side is drawn out to the outside.

[0030] Each part of the all-solid-state battery of this embodiment will be described in detail below.

[0031] The base material layer 11 of the exterior packaging material 1 is composed of a heat-resistant resin film having a thickness of 5 μm to 50 μm. The resin that composes this base material layer 11 can be suitably selected from oriented polyamide film, oriented polyester (PET, PBT, PEN, etc.), oriented polyolefin (OPP, etc.), etc.

[0032] The metal foil layer 12 has a thickness set to 5 μm to 120 μm, and has a function of blocking the intrusion of oxygen and moisture from the surface (outer surface) side. Aluminum foil, SUS foil (stainless steel foil), copper foil, nickel foil, etc. can be suitably used as this metal foil layer 12. In this embodiment, the terms "aluminum", "copper", and "nickel" are used to include their alloys.

[0033] Furthermore, by subjecting the metal foil layer 12 to a plating process or the like, the risk of pinholes occurring can be reduced, and the function of blocking the intrusion of oxygen and moisture can be further improved.

[0034] Furthermore, if the metal foil layer 12 is subjected to a chemical conversion treatment such as chromate treatment, the corrosion resistance is further improved, making it possible to more reliably prevent defects such as chipping, and also to improve adhesion to the resin, thereby further improving durability.

[0035] The sealant layer (thermally adhesive resin layer) 15 has a thickness set to 20 μm to 100 μm and is made of a film of a thermally adhesive (thermally adhesive) resin. Suitable resins for the sealant layer 15 include polyethylene (LLDPE, LDPE, HDPE), polyolefins such as polypropylene, cyclic polyolefins, olefin copolymers, acid-modified products thereof, and ionomers, such as non-oriented polypropylene (CPP, IPP).

[0036] Considering that electricity is taken out using a tab lead, that is, in consideration of sealing properties and adhesiveness with the tab lead, it is preferable to use a polypropylene resin (non-oriented polypropylene film (CPP, IPP)) as the sealant layer 15.

[0037] The gas barrier layer 13 is made of a resin film having heat resistance and insulating properties. The resin for the gas barrier layer 13 may be selected from the group consisting of polyamide (6-nylon, 66-nylon, MXD nylon, etc.), polyester (PET, PBT, PEN), polyvinylidene chloride (PVDC), polyethylene (LLDPE, LDPE, HDPE), polypropylene (CPP, OPP), polyolefins such as polypropylene, olefin copolymers, acid-modified products thereof, and ionomers.

[0038] In this embodiment, the thickness of the gas barrier layer 13 is preferably set to 3 μm to 50 μm, and more preferably to 10 μm to 40 μm. In other words, when the thickness of the gas barrier layer 13 is set in this range, the permeation suppression effect of hydrogen sulfide gas and water vapor gas can be reliably obtained, and even if the sealant layer 15 melts and flows out due to thermal adhesion, the gas barrier layer 13 can reliably ensure insulation. In other words, if the gas barrier layer 13 is too thin, there is a risk that the gas permeation suppression effect and insulation cannot be ensured, which is not preferable. Conversely, if the gas barrier layer 13 is too thick, not only cannot the exterior material 1 be thinned, but also the effect of making it thicker than necessary cannot be fully obtained, which is not preferable.

[0039] In this embodiment, it is preferable to use a resin film as the gas barrier layer 13. That is, the entire film becomes a barrier layer, and therefore, unlike a vapor deposition film, no barrier cracks occur and the barrier properties can be improved.

[0040] Furthermore, a non-stretched film or a stretched film may be used as the resin film constituting the gas barrier layer 13, and it is particularly preferable to use a stretched film. That is, when a stretched film is used, the heat resistance, insulating properties, formability, and gas barrier properties can be further improved.

[0041] The gas barrier layer 13 of this embodiment has good insulating properties, and maintains good insulating properties even after the all-solid-state battery body 5 is encapsulated (sealed) with the case body 3 and the blocking member 4 as the exterior material 1 of this embodiment.

[0042] In this embodiment, the resin constituting the gas barrier layer 13 has a water vapor transmission rate of 50 (g / m2) or more, measured in accordance with JIS K7129-1 (humidity sensor method at 40° C. and 90% Rh). 2 / day), i.e., the water vapor transmission rate is 50 (g / m 2 / day) or less, the gas permeation prevention effect of the gas barrier layer 13 can prevent the intrusion of moisture such as water vapor gas from the outside, thereby suppressing the generation of hydrogen sulfide gas due to the reaction between moisture and the solid electrolyte, and more reliably preventing the leakage of hydrogen sulfide gas and the like.

[0043] In this embodiment, it is preferable to use a resin having a thermal conductivity of 0.2 W / m·K or more as the resin constituting the gas barrier layer 13. That is, when this configuration is adopted, the heat transfer property of the gas barrier layer 13 can be sufficiently ensured, and the cooling property of the all-solid-state battery body 5 can be further improved.

[0044] Furthermore, in this embodiment, it is preferable to adopt a resin constituting the gas barrier layer 13 that has a melting point 10° C. or more higher than that of the resin constituting the sealant layer 15. In other words, when the gas barrier layer 13 has a high melting point, there is no change in the thickness of the gas barrier layer 13 during heat sealing after the solid-state battery is housed, the water vapor permeation prevention effect of the gas barrier layer 13 can be well maintained, and the generation of hydrogen sulfide gas can be more reliably suppressed. In this embodiment, the melting point is measured by the melting peak temperature of DSC measured in accordance with JIS K7121-1987.

[0045] In this embodiment, two-component curing adhesives for dry lamination, such as polyurethane adhesives, acrylic adhesives, polyacrylate adhesives, modified polypropylene adhesives, polyester adhesives, polyamide adhesives, and epoxy adhesives, can be suitably used as the first adhesive layer that bonds the base layer 11 and the metal foil layer 12, the second adhesive layer that bonds the metal foil layer 12 and the gas barrier layer 13, and the third adhesive layer 14 that bonds the gas barrier layer 13 and the sealant layer 15. The thicknesses of these first to third adhesive layers are preferably set to 1 μm to 6 μm.

[0046] In this embodiment, the second adhesive layer that bonds the metal foil layer 12 and the gas barrier layer 13 can be formed by using an adhesive resin (polyolefin-based resins such as polyolefins, carboxylic acid-modified polyolefins, and metal-modified polyolefins, polyvinyl acetate-based resins, (meth)acrylic resins, amino resins, etc.) instead of an adhesive, and laminating the adhesive resin and the resin that forms the gas barrier layer 13 on the metal foil layer 12 by co-extruding them (extrusion lamination method), or by forming a laminate in which the adhesive resin and the gas barrier layer 13 are laminated in advance, and laminating this laminate on the metal foil layer 12 by a thermal lamination method, or by pouring molten adhesive resin between the metal foil layer 12 and the gas barrier layer 13 while bonding the metal foil layer 12 and the gas barrier layer 13 together (sand lamination method), or the like.

[0047] In this embodiment, the opening 2 on the case body 3 side has its outer peripheral edge 21 provided on the flange 33 of the case body 3. Furthermore, the opening 2 on the closing member 4 side has its opening edge 21 formed to correspond to the opening edge 21 of the opening 2 of the case body 3.

[0048] In this embodiment, the opening 2 formed in the case body 3 and the blocking member 4 is not provided with any adhesive that constitutes the adhesive layer 14, and the gas barrier layer 13 is exposed (exposed) to the inside through the opening 2. In a state in which the all-solid-state battery is fabricated, the gas barrier layer 13 is disposed so as to face the upper surface, peripheral side surface and lower surface of the all-solid-state battery body 5.

[0049] Next, a method for manufacturing the exterior material 1 in this embodiment will be described. Needless to say, in the present invention, the method for manufacturing the exterior material 1 is not limited (the same applies to the method for manufacturing the case body 3 and the method for manufacturing the all-solid-state battery, which will be described later).

[0050] In this embodiment, first, a laminate without a sealant layer is produced, for example, by a dry lamination method. That is, a resin film for the base layer 11 is bonded via an adhesive to the outer surface of a metal foil for the metal foil layer 12, which has been subjected to a base treatment and a chemical conversion treatment as necessary, and a resin film for the gas barrier layer 13 is bonded via an adhesive to the inner surface of the metal foil, thereby producing a laminate without a sealant layer in which the metal foil layer 12 and the gas barrier layer 13 are laminated on the inner surface side of the base layer 11.

[0051] In addition, when producing a laminate without a sealant layer, it is possible to produce it by a method other than the dry lamination method, such as the extrusion lamination method, as described above. For example, the above laminate may be produced by extruding and laminating the resin composition for the base layer 11 and the resin composition for the gas barrier layer 13 onto the inner and outer surfaces of a metal foil, respectively.

[0052] Next, the adhesive that constitutes the adhesive layer 14 is applied to the inner surface of the laminate without the sealant layer (the inner surface of the gas barrier layer 13) using a gravure roll or the like. During this application, the adhesive is applied to the inner surface of the gas barrier layer 13 except for the portion (planned opening portion 2a) where the opening 2 in the sealant layer 15 is to be formed, forming an adhesive-coated portion 14a, while the adhesive is not applied to the portion corresponding to the planned opening portion 2a, forming an adhesive-uncoated portion 14b.

[0053] A resin film for a sealant layer is attached to the inner surface of the gas barrier layer 13 having the adhesive-uncoated portion 14b via the adhesive layer 14 (adhesive-coated portion 14a) and dried. The resin film for a sealant layer is also provided in the portion corresponding to the adhesive-uncoated portion 14b.

[0054] 6, the area between the adhesive-coated portion 14a and the intended opening portion 2a is cut away, and the intended opening portion 2a, which is the sealant layer 15 of the adhesive-uncoated portion 14b, is cut away to form the opening 2. This cutting method is performed using a laser cutter, a roll blade, a punching blade (Thomson blade, etching blade, etc.), an ultrasonic cutter, etc. Among these, it is preferable to use a laser cutter, which can perform processing with high precision.

[0055] In this embodiment, as shown in Figs. 5A and 5B, it is preferable to automatically cut out the sealant layer 15 at the intended opening portion 2a using an opening position detection device 81 and a laser cutting device 82 to form the opening 2.

[0056] That is, the opening position detection device 81 detects the boundary position between the adhesive coated portion 14a and the adhesive uncoated portion 14b, and is equipped with a detection sensor such as a photoelectric sensor that detects the amount of reflected light of light irradiated from a light source onto the subject, and detects the boundary position between the adhesive coated portion 14a and the adhesive uncoated portion 14b based on the difference in the amount of light, etc. For example, light is irradiated from the light source of the opening position detection device 81 towards the subject (exterior material 1), and the boundary is detected based on the reflected light of that light. 5B, light X1 and X2 irradiated from the light source toward the adhesive-coated portion 14a of the exterior material 1 passes through the adhesive-coated portion 14a to become reflected light Y1 and Y2 reflected from the surface of the gas barrier layer 13 (the interface between the adhesive-coated portion 14a and the gas barrier layer 13) and the surface of the adhesive-coated portion 14a, and light X3 irradiated from the light source toward the adhesive-uncoated portion 14b of the exterior body 1 passes through the adhesive-uncoated portion (gap portion) 14b to become reflected light Y3 reflected from the surface of the gas barrier layer 13. The reflected light Y1 and Y2 from the adhesive-coated portion 14a and the reflected light Y3 from the adhesive-uncoated portion 14b have different light amounts, as described below, and the boundary position between the adhesive-coated portion 14a and the adhesive-uncoated portion 14b is detected based on this difference in light amount.

[0057] Moreover, the laser cutting device 82 is composed of a CO2 laser cutting device or the like, and based on position information from the opening position detection device 81, cuts the boundary position between the adhesive-coated portion 14a and the adhesive-uncoated portion 14b, i.e., the outer peripheral edge portion 21a of the intended opening portion 2a, and cuts off the sealant layer 15 of the intended opening portion 2a to form the opening 2. In this way, the opening 2 is automatically formed in the exterior material 1 to produce an exterior material with an opening. Therefore, by using the opening position detection device 81 and the laser cutting device 82, the opening 2 can be automatically formed in the exterior material 1 to produce an exterior material with an opening.

[0058] In the exterior material 1 before the opening 2 of this embodiment is formed, when the L value, which is the lightness of the adhesive-coated portion 14a measured from the sealant layer 15 side (inner surface side), is "La" and the L value, which is the lightness of the adhesive-uncoated portion 14b, is "Lb", it is preferable to set the absolute position of ΔL (lightness difference) as the absolute value of the difference between La and Lb to 0.5 or more. In other words, it is preferable to configure so that the relational expression |La-Lb|=ΔL≧0.5 holds.

[0059] In other words, by satisfying the above relational expression, the brightness difference ΔL between the adhesive-coated portion 14a and the adhesive-uncoated portion 14b is large, and therefore the difference in light intensity between the reflected light Y1, Y2 from the adhesive-coated portion 14a and the reflected light Y3 from the adhesive-uncoated portion 14b (see Figure 5B) becomes large, and the boundary position between the adhesive-coated portion 14a and the adhesive-uncoated portion 14b can be accurately and appropriately captured by the above-mentioned photoelectric sensor, thereby making it possible to form an opening 2 with high precision.

[0060] In this embodiment, a spectrophotometer such as a CM-2500C manufactured by Konica Minolta can be suitably used to measure the L value of the adhesive-coated portion 14a and the L value of the adhesive-uncoated portion 14b.

[0061] In this embodiment, when measuring the color difference (L value), the specular reflection stipulated in 4.1.2 or 4.2.2 of Section 5 of Part 4 of the General Test Method for Coating Films in JIS K 5600-4-5 (1999 Edition) is excluded, and the color difference (L value) is measured according to the CIE 1976 (L * a * b * The color of the test sample was measured using the color coordinates (lightness L, chroma a, hue b). CIE stands for Commission Internationale de l'Eclairage (International Commission on Illumination).

[0062] In this embodiment, the external haze of the gas barrier layer 13 is preferably adjusted to 20 or more. That is, light entering the gas barrier layer (resin) 13 from the adhesive-coated portion (resin) 14a passes through the resin / resin interface and has a narrow refractive index range, while light entering the gas barrier layer (resin) 13 from the adhesive-uncoated portion (air) 14b passes through the air / resin interface and has a wide refractive index range. As a result, as shown in Fig. 5B, light X1 and X2 irradiated to the adhesive-coated portion 14a are not easily diffused when reflected on the surface of the gas barrier layer 13 (the interface with the adhesive-coated portion 14a) or the surface of the adhesive-coated portion 14a, whereas light X3 irradiated to the adhesive-uncoated portion 14b is easily diffused when reflected on the surface of the gas barrier layer 13. Therefore, when the external haze of the gas barrier layer 13 is large, such as 20 or more, the difference in light intensity between the reflected light Y1, Y2 from the adhesive-coated portion 14a and the reflected light Y3 from the adhesive-uncoated portion 14b becomes large, and the photoelectric sensor can accurately and appropriately capture the boundary position between the adhesive-coated portion 14a and the adhesive-uncoated portion 14b, thereby forming a highly accurate opening 2.

[0063] Here, the haze of the gas barrier layer 13 includes a total haze, an internal haze, and an external haze, and these hazes have the following relationship: total haze (%) = internal haze (%) + external haze (%). In this embodiment, the total haze and the internal haze are calculated, and the value obtained by subtracting the internal haze from the total haze is used as the external haze.

[0064] When measuring haze, a film (film sample) for the gas barrier layer is used. The haze (total haze) of this film sample is measured in accordance with JIS K 7136:2000 (Method of determining haze for plastics - transparent materials). When measuring internal haze, silicone oil is applied to both sides of the film sample, and the film sample with oil is sandwiched between glass plates and measured to determine the haze (internal haze) with the external haze factor due to the unevenness of the film surface removed. The external haze is calculated based on the film haze (total haze) and internal haze thus obtained.

[0065] In this embodiment, the haze of the gas barrier layer 13 can be suitably measured using a Murakami Color Research Laboratory HAZEMETER HM-150 or the like.

[0066] Furthermore, in this embodiment, it is preferable to adjust the total haze of the sealant layer 15 to be equal to or less than 10. In other words, when the total haze of the sealant layer 15 is equal to or less than 10, the amount of reflected light Y1 to Y3 is hardly affected by the haze of the sealant layer 15, so that the boundary position between the adhesive-coated portion and the adhesive-uncoated portion can be accurately detected by the photoelectric sensor based on the difference in light amount due to diffusion of the reflected light Y1 to Y3 from the gas barrier layer 13, and the opening 2 can be formed with higher accuracy.

[0067] In this embodiment, the haze of the sealant layer 15 can be suitably measured using a Murakami Color Research Laboratory HAZEMETER HM-150 or the like.

[0068] In this embodiment, it is preferable to adjust the arithmetic mean height Sa of the gas barrier layer 13 to 0.2 μm or more. That is, when the arithmetic mean height Sa of the gas barrier layer 13 is 0.2 μm or more, as in the case of adjusting the haze, the light X1 and X2 irradiated to the adhesive coated portion 14a is not easily diffused when reflected on the surface of the gas barrier layer 13 (the interface with the adhesive coated portion 14a) or the surface of the adhesive coated portion 14a, as shown in FIG. 5B, whereas the light X3 irradiated to the adhesive uncoated portion 14b is easily diffused when reflected on the surface of the gas barrier layer 13. Therefore, the difference in the amount of light between the reflected light Y1 and Y2 from the adhesive coated portion 14a and the reflected light Y3 from the adhesive uncoated portion 14b becomes large, and the photoelectric sensor can accurately and appropriately capture the boundary position between the adhesive coated portion 14a and the adhesive uncoated portion 14b, and the opening 2 can be formed with high accuracy.

[0069] In this embodiment, the arithmetic mean height Sa is measured by observing the sample surface (gas barrier layer surface) with a white light interferometer according to the method defined in ISO25178 to determine the arithmetic mean height Sa.

[0070] In this embodiment, the arithmetic mean height Sa of the gas barrier layer 13 can be suitably measured using a white light interferometer VS1330 manufactured by Hitachi High-Tech Science or the like.

[0071] In this embodiment, it is preferable to adjust the arithmetic mean height Sa of the sealant layer 15 to less than 0.2 μm. In other words, when the arithmetic mean height Sa of the sealant layer 15 is less than 0.2 μm, the arithmetic mean height Sa of the sealant layer 15 has almost no effect on the amount of reflected light Y1 to Y3, so that the photoelectric sensor can accurately detect the boundary position between the adhesive-coated portion and the adhesive-uncoated portion based on the difference in light amount due to diffusion of the reflected light Y1 to Y3 from the gas barrier layer 13, and the opening 2 can be formed with even higher accuracy.

[0072] In this embodiment, the arithmetic mean height Sa of the sealant layer 15 can be suitably measured using a white light interferometer VS1330 manufactured by Hitachi High-Tech Science or the like.

[0073] In this embodiment, the gloss value of the gas barrier layer 13 needs to be adjusted to 100 or less. That is, when the gloss value of the gas barrier layer 13 is 100 or less, as in the case of adjusting the haze and the arithmetic mean height Sa, as shown in FIG. 5B, the light X1, X2 irradiated to the adhesive-coated portion 14a is not easily diffused when reflected on the surface of the gas barrier layer 13 (the interface with the adhesive-coated portion 14a) or the surface of the adhesive-coated portion 14a, whereas the light X3 irradiated to the adhesive-uncoated portion 14b is easily diffused when reflected on the surface of the gas barrier layer 13. For this reason, the difference in the amount of light between the light Y1, Y2 reflected from the adhesive-coated portion 14a and the light Y3 reflected from the adhesive-uncoated portion 14b becomes large, and the photoelectric sensor can accurately and appropriately capture the boundary position between the adhesive-coated portion 14a and the adhesive-uncoated portion 14b, and the opening 2 can be formed with high accuracy.

[0074] In this embodiment, the gloss value is a value measured at an incidence angle of 60° in accordance with JIS Z 8741:1997.

[0075] In this embodiment, the gloss value of the gas barrier layer 13 can be suitably measured using a tool such as micro-TRI-gloss-s manufactured by BYK.

[0076] In this embodiment, the gloss value of the sealant layer 15 is preferably adjusted to a value exceeding (excluding) 100. In other words, when the gloss value of the sealant layer 15 exceeds 100, the difference in the amount of light between the reflected light Y1, Y2 from the adhesive-coated portion 14a and the reflected light Y3 from the adhesive-uncoated portion 14b is enhanced, thereby making it possible to further improve the detectability by the photoelectric sensor.

[0077] In this embodiment, the gloss value of the sealant layer 15 can be suitably measured using a tool such as micro-TRI-gloss-s manufactured by BYK.

[0078] Next, a method of molding the sheet-like exterior material with an opening obtained as described above to produce the case body 3 will be described. First, as shown in Fig. 6, the sheet-like exterior material 1 for the case body before molding includes a top wall planned portion 31a which is a portion intended to become the top wall 31, a side wall planned portion 32a which is a portion intended to become the side wall 32, and a flange planned portion 33a which is a portion intended to become the flange 33.

[0079] In this embodiment, the outer circumferential edge portion 21a of the intended opening portion 2a is set within the range of the intended flange portion 33a.

[0080] 7 is a schematic cross-sectional view showing a mold device for molding a case body 3 using an opening-equipped exterior material 1. As shown in the figure, this mold device includes a die 6 as an upper mold, and a punch 7 and a blank holder 70 as a lower mold.

[0081] The die 6 has a molding recess 65 formed on its lower surface for molding the accommodation portion 35 (the top wall 31 and the side wall 32) of the case body 3.

[0082] The punch 7 is disposed in correspondence with the molding recess 65 of the die 6 , and the blank holder die 70 is disposed on the outer periphery of the punch 7 and faces the outer periphery of the lower surface of the die 6 .

[0083] Then, the opening-equipped exterior material 1 as a molding material is placed so that its side wall planned portion 32a corresponds to the tip outer peripheral edge portion of the punch 7. In this state, the flange planned portion 33a of the exterior material 1 is sandwiched and supported by the outer peripheral portion of the die 6 and the blank holding die 70, and the punch 7 is driven into the molding recess 65 of the die 6, whereby the exterior material 1 is pressed. As a result, a case body molded body (molding material) having a concave storage portion 35 (top wall 31 and side wall 32) and a flange 33 on the outside of the storage portion 35 is molded. Next, the flange 33 of the molded body is cut to a predetermined size, thereby producing the case body 3 of this embodiment. In this case body 3, the opening 2 is arranged in the entire area of ​​the storage portion 35, and the outer peripheral edge portion 21 of the opening 2 is arranged in the flange 33, as shown in Figures 1 to 3.

[0084] As shown in Figs. 1 to 3, in this embodiment, the solid-state battery body 5 is packaged using the case body 3 and the sheet-like blocking member 4 to manufacture an all-solid-state battery. That is, the all-solid-state battery body 5 is accommodated in the accommodation portion 35 of the case body 3, and the blocking member 4 is arranged so as to block the opening of the accommodation portion 35 from the lower side, and the sealant layer 15 of the flange 33 of the case body 3 and the sealant layer 15 of the outer peripheral edge of the blocking member 4 are arranged so as to face and overlap each other. In this state, the flange 33 of the case body 3 and the outer peripheral edge of the blocking member 4 are sandwiched between a pair of sealing dies and heated. As a result, the sealant layers 15 that overlap each other are heat-sealed and joined together, and an all-solid-state battery in which the all-solid-state battery body 5 is accommodated in an airtight state in the case body 3 and the blocking member 4 is manufactured.

[0085] According to the all-solid-state battery of the present embodiment having the above-mentioned configuration, the gas barrier layer 13 is provided between the metal foil layer 12 and the sealant layer 15 in the case body 3 and the closing member 4, and the opening 2 is formed in the top wall 31 and the side wall 32 by removing a part of the sealant layer 15. Therefore, heat generated from the all-solid-state battery body 5 is efficiently transferred to the metal foil layer 12 via the opening 2 and the gas barrier layer 13 without being blocked by the sealant layer 15, and is dissipated, thereby ensuring sufficient heat dissipation and cooling properties.

[0086] In particular, in this embodiment, the outer peripheral edge 21 of the opening 2 in the case body 3 is set to the flange 33 of the case body 3, so that a large opening 2 corresponding to almost the entire area of ​​the all-solid-state battery body 5 can be formed, and heat dissipation and cooling properties can be further improved.

[0087] Furthermore, in this embodiment, by specifying the difference in gloss value and L value between the adhesive coated portion 14a and the adhesive uncoated portion 14b of the exterior material 1, the haze value of the gas barrier layer 13 and the sealant layer 15, the arithmetic mean height Sa of the gas barrier layer 13 and the sealant layer 15, and the gloss value of the gas barrier layer 13 and the sealant layer 15, as described above, it is possible to increase the difference in light intensity between the reflected light Y1, Y2 from the adhesive coated portion 14a and the reflected light Y3 from the adhesive uncoated portion 14b, and the boundary position between the adhesive coated portion 14a and the adhesive uncoated portion 14b can be accurately and appropriately detected by the photoelectric sensor, thereby more reliably forming a high-precision opening 2.

[0088] Moreover, according to the all-solid-state battery of this embodiment, since the gas barrier layer 13 is disposed on the inner surface side of the metal foil layer 12, even if the solid electrolyte of the all-solid-state battery body 5 reacts with moisture in the outside air to generate hydrogen sulfide gas or the like, the gas can be reliably prevented from leaking by the gas barrier layer 13. Furthermore, the gas permeation prevention effect of the gas barrier layer 13 can prevent the intrusion of moisture such as water vapor gas from the outside, so that the generation of hydrogen sulfide gas itself due to the reaction between the moisture and the solid electrolyte can be suppressed, and the leakage of hydrogen sulfide gas or the like can be more reliably prevented.

[0089] In the all-solid-state battery of this embodiment, in the portion where the opening 2 is formed, although there is no sealant layer 15 between the all-solid-state battery body 5 and the metal foil layer 12, the gas barrier layer 13 having insulating properties is disposed therebetween, and therefore, the gas barrier layer 13 can reliably ensure insulation.

[0090] Furthermore, when cutting the exterior material 1 with a laser cutter or the like to form the opening 2, a damaged portion caused by the laser is formed on the outer peripheral edge 21 of the opening, which may cause defects such as cracks and pinholes. However, in this embodiment, the outer peripheral edge 21 of the opening is formed on the flange 33 of the case body 3, so that the adverse effects of the damaged portion can be avoided. That is, the flange 33 of the case body 3, which is a molded body, is heat-sealed, so that a resin reservoir formed by the heat seal is formed on the damaged portion (the outer peripheral edge 21 of the opening). Therefore, the damaged portion can be covered and repaired by the resin reservoir, so that the adverse effects of the damaged portion caused by laser cutting can be reliably avoided.

[0091] Furthermore, in the all-solid-state battery of this embodiment, the sealant layer 15 is not formed in the portion of the exterior material 1 that corresponds to the all-solid-state battery body 5, and therefore the space for accommodating the all-solid-state battery body 5 can be made larger (thicker). Therefore, in the all-solid-state battery of this embodiment, compared to conventional all-solid-state batteries, a larger-sized all-solid-state battery body 5 can be accommodated without changing the external dimensions of the case body 3, and therefore high output and high capacity can be achieved while achieving a thin design.

[0092] In addition, in the all-solid-state battery of this embodiment, the sealant layer 15 is provided on the flange 33 provided around the entire periphery of the case body 3, and therefore the sealant layer 15 provided around the entire periphery can reliably seal the entire periphery of the all-solid-state battery, thereby ensuring good sealing performance.

[0093] In the above-described all-solid-state battery of this embodiment, the case where the opening 2 is formed in both the case body 3 and the blocking member 4 has been described as an example. However, the present invention is not limited to this. As shown in FIG. 8 , the opening 2 may be formed in the case body 3, and the opening 2 may not be formed in the blocking member 4.

[0094] In addition, the all-solid-state battery of this embodiment shown in FIG. 1 is arranged so that the case body 3 is disposed on the upper side and the blocking member 4 is disposed on the lower side, but the present invention is not limited to this. In other words, the all-solid-state battery shown in FIG. 1 may be inverted, that is, the case body 3 which is a molded body is disposed on the lower side and the sheet-like blocking member 4 is disposed on the upper side.

[0095] In the above embodiment, the edge 21 of the opening 2 is set within the flange 33, but the present invention is not limited to this. For example, in the present invention, the edge 21 of the opening 2 may be set on the side wall 32 of the case body 3 as shown in Fig. 9, or the edge 21 of the opening 2 may be set on the top wall (bottom wall) 33 of the case body 3 as shown in Fig. 10. In other words, the shape and size of the opening 2 are not particularly limited in the present invention.

[0096] Furthermore, in the present invention, a molded body may be used as the blocking member 4. For example, as shown in Fig. 11, a tray-shaped molded body having a shape obtained by inverting the case body 3 upside down may be used as the blocking member 4, and the casing of the all-solid-state battery may be formed by the case body 3 which is a molded body and the tray-shaped blocking member 4 which is a molded body. In this case, by using a similar configuration for the blocking member 4 as the case body 3, the same effect can be obtained with the blocking member 4.

[0097] In the above embodiment, a case has been described in which an all-solid-state battery is used as the power storage device of the present invention. However, the present invention is not limited to this, and can be applied to power storage devices other than all-solid-state batteries. EXAMPLES

[0098] [Table 1]

[0099] <Example 1> As a sample (exterior material), a laminate material was prepared in which a base layer / first adhesive layer / metal foil layer / second adhesive layer / gas barrier layer / third adhesive layer / sealant layer were laminated in this order from the outer surface side. That is, a 25 μm thick stretched nylon film (ONY) was laminated as a base layer on the outer surface (glossy surface) of an aluminum foil made of A8079-O specified in JIS H4160 and having a thickness of 40 μm as a metal foil layer, via a two-component curing polyester-urethane adhesive as a first adhesive layer. In addition, a 12 μm thick matte PET (polyethylene terephthalate) film was laminated as a gas barrier layer on the inner surface (matte surface) of the metal foil layer, as shown in Table 1, via a two-component curing polyester-urethane adhesive as a second adhesive layer. Furthermore, as shown in Table 1, a 80 μm thick CPP (unstretched polypropylene: CPP(1)) film was laminated as a sealant layer on the inner surface of the gas barrier layer, via a two-component curing polyester-urethane adhesive as a third adhesive layer. At this time, the third adhesive layer was not applied to the intended opening portion. The size of this adhesive-uncoated portion (intended opening portion) was a rectangle of 100 mm×200 mm (see FIG. 4 and FIG. 5A, etc.).

[0100] The thus obtained laminated film (laminate material) was cured at 40° C. for 5 days after each layer was laminated together to produce a sample (exterior material) of Example 1.

[0101] For the sample of Example 1, the L value (Lb) of the adhesive uncoated part (the part to be opened) and the L value (La) of the adhesive coated part were measured from the inner surface side using a spectrophotometer (CM-2500c) manufactured by Konica Minolta, and the lightness difference (ΔL = |La - Lb|) between the adhesive uncoated part and the adhesive coated part was calculated. Furthermore, as shown in Table 1, the haze, arithmetic mean height Sa, and gloss value of each resin film were measured by the method described in the above embodiment.

[0102] [Table 2]

[0103] Table 2 shows the relationship between the types of resin films for the gas barrier layer and the resin films for the sealant layer used in Example 1 (including the following Examples 2 to 6 and Comparative Examples 1 to 3), as well as the product names and main physical properties.

[0104] <Examples 2 to 6 and Comparative Examples 1 to 3> Except for using the gas barrier layer film and the sealant layer resin film shown in Table 1, samples (exterior materials) with adhesive uncoated areas were prepared in the same manner as in Example 1 above for Examples 2 to 6 and Comparative Examples 1 to 3, and the lightness difference ΔL, haze, arithmetic mean height Sa, and gloss value were similarly determined. The results are also shown in Table 1.

[0105] <Evaluation of opening formation and detectability> In addition, for each of the above examples and comparative examples, an opening forming device consisting of an opening position detection device and a laser cutting device (see FIG. 5A) was used to remove the sealant layer from the intended opening portion (adhesive uncoated portion).

[0106] The opening position detection device used was an MR101 scanning head manufactured by Nireco Corporation. This detection device uses an LED as a light source, and detects the outer periphery of the colored adhesive uncoated area (planned opening area) based on a mechanism that receives the difference in the amount of light reflection (light amount) between the colored adhesive uncoated area and the colored adhesive coated area with an SPD (silicon photodiode), which is a photoelectric sensor, and outputs a voltage proportional to the amount of light.

[0107] A CO2 laser cutting device was used as the laser cutting device. Based on the position information of the colored adhesive uncoated part (planned opening part) in the center of each sample detected by the opening position detection device, this cutting device cuts and removes only the sealant layer (CPP film) on the colored adhesive uncoated part, creating an exposed part (opening) of the gas barrier layer (matte PET film) measuring 100 mm wide x 200 mm long.

[0108] In the detectability shown in Table 1, "○" indicates that the peripheral position of the uncoated adhesive portion was accurately detected and an opening was formed with good precision, while "×" indicates that the peripheral position of the uncoated adhesive portion could not be adequately detected and an opening could not be formed.

[0109] <Evaluation Results> As is clear from Table 1, in the samples of Examples 1 to 6, the opening position detection device was able to accurately detect the adhesive-uncoated parts, and the laser cutting device was able to precisely cut and remove the sealant layer (CPP film) on the adhesive-uncoated parts, forming highly accurate openings. In contrast, in the samples of Comparative Examples 1 to 3, the opening position detection device was unable to detect the adhesive-uncoated parts, the laser cutting device did not work, and the adhesive-uncoated parts could not be removed. [Industrial Applicability]

[0110] The exterior packaging material for an electricity storage device of the present invention can be suitably used as a material for a battery case (casing) for housing an all-solid-state battery main body such as an all-solid-state battery. [Explanation of symbols]

[0111] 1: Exterior material 11: Base material layer 12: Metal foil layer 13: Gas barrier layer 14:Adhesive layer (3rd adhesive layer) 14a: Adhesive coating section 14b: Uncoated with adhesive 15: Sealant layer 2: Opening 2a: Opening area 3: Case body 35: Storage unit 4: Closure member 5: All-solid battery body

Claims

1. An exterior material for an electricity storage device, comprising: a resin base layer; a metal foil layer laminated on an inner surface side of the base layer; a gas barrier layer laminated on the inner surface side of the metal foil layer; and a resin sealant layer laminated on the inner surface side of the gas barrier layer via an adhesive layer, the sealant layer is provided with a planned opening portion into which an opening is to be formed by removing a sealant layer resin; the adhesive layer is provided with an adhesive-uncoated portion that is provided in correspondence with the intended opening portion and in which no adhesive is present, and an adhesive-coated portion that is provided in correspondence with a portion other than the intended opening portion and in which adhesive is present; The gas barrier layer has a gloss value of 100 or less when measured at an incidence angle of 60° in accordance with JIS Z 8741:1997.

2. 2. An electrical storage device packaging material with an opening, comprising: the sealant layer in the electrical storage device packaging material according to claim 1; and an opening formed in the sealant layer by removing the resin for the sealant layer in the intended opening portion.

3. An electricity storage device comprising the exterior material for an electricity storage device according to claim 1 and an electricity storage device main body exteriorly covered with the exterior material for an electricity storage device, An opening is formed in the sealant layer of the electrical storage device exterior material by removing the sealant layer resin from the intended opening portion, and The power storage device, wherein the opening is disposed opposite to the power storage device body.

4. a case body having a recessed accommodation portion in which the power storage device main body is accommodated; and a closing member attached to the case body in a state in which the closing member closes an open portion of the accommodation portion, The electricity storage device according to claim 3 , wherein at least one of the case body and the closing member is made of the exterior material for an electricity storage device.

Citation Information

Patent Citations

  • Outer packaging material for power storage device

    JP2020187835A

  • Laminate sheet for sulfide-based all-solid-state battery and laminate pack using the same

    JP2020187855A

  • Exterior material for all-solid-state battery, manufacturing method thereof, and all-solid-state battery

    JP6747636B1

  • Exterior material for all-solid-state battery, manufacturing method thereof, and all-solid-state battery

    JP6777276B1

  • All-solid-state battery sheathing material and all-solid-state battery

    WO2023022087A1